Training‐induced mitochondrial adaptation: role of peroxisome proliferator‐activated receptor γ coactivator‐1α, nuclear factor‐κB and β‐blockade. Issue 3 (17th December 2012) - Feng, Hong; Kang, Chounghun; Dickman, Jonathan R.; Koenig, Ryan; Awoyinka, Iwalola; Zhang, Yong; Ji, Li Li
Abstract : Interaction of peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α) with other cellular signalling pathways plays an important role in training‐induced mitochondrial adaptations. The purpose of this study was to examine whether pyrolidine dithiocarbamate (PDTC), a nuclear factor‐κB inhibitor and antioxidant, and the β‐adrenergic blocker propranolol would affect the PGC‐1α‐induced mitochondrial transcription factors, enzymes and proteins involved in energy metabolism and antioxidant defense in response to endurance training. Female Sprague–Dawley rats (aged 8 weeks) were randomly divided into two groups ( n = 24), one subjected to 8 weeks of treadmill training and one remaining sedentary. Each group of rats was subdivided in to three groups that were injected (i.p .) daily with PDTC (50 mg (kg body weight) −1 ), propranolol (30 mg kg −1 ) or saline as a control 1 h before the daily exercise session. Sedentary PDTC‐treated rats showed 75% higher PGC‐1α content ( P < 0.01) but lower mitochondrial transcription factor A and phosphorylated cAMP‐responsive element binding protein (p‐CREB) than control rats. Training increased PGC‐1α by 57% ( P < 0.01), cytochrome c oxidase 4 by 30% ( P < 0.05) and p‐CREB by 13% ( P < 0.05), whereas the mitochondrial mitofusin‐2 level was decreased by 24% ( P < 0.01). Treatment with PDTC decreased PGC‐1α and p‐CREB content by 34 and 53% ( P < 0.05), respectively, in trained rats and abolished training effects on cytochrome c oxidase 4 and mitochondrial mitofusin‐2. None of the training effects was abolished by propranolol treatment. Mitochondrial superoxide dismutase activity was decreased with PDTC, whereas training‐induced glutathione peroxidase activity was unaltered by either drug. The data indicates that nuclear factor‐κB‐inhibitory and antioxidant properties of PDTC can attenuate PGC‐1α‐mediated mitochondrial adaptation to endurance training, whereas the β‐adrenergic pathway has little adverse effect.